Penegakan Hukum Terhadap Pengemudi Truk Yang Melanggar Rambu Larangan Melintas (Studi Kasus Di Jimbaran) - I Made Gede Wiradana; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Fakultas Hukum Universitas Warmadewa, 2025)
Traffic accidents in Jimbaran gong cave by truck drivers who violated the no-crossing sign due to a lack of public awareness. The formulation of the problem in this study is 1) How is law enforcement against truck drivers who violate the prohibition sign in Jimbaran village, Bali? and 2) What are the legal remedies and obstacles faced by law enforcement officials against violations of no-passing signs by truck drivers in Jimbaran village, Bali? Empirical legal research methods and using a case problem approach. Empirical research method and using case problem approach. The results of the discussion Traffic law enforcement in Jimbaran, carried out with a preventive and repressive approach. Preventive efforts include setting, guarding, and patrolling traffic. Repressive adopted an educative approach and Restorative Justice for the peaceful settlement of the accident case. Interviews with police officers revealed serious violations especially by trucks causing fatal accidents. Despite the amicable settlement, criminal penalties still apply as per the Criminal Code (KUHP). The Jimbaran Traffic Unit has a role in law enforcement despite facing obstacles such as low public awareness, lack of facilities, and internal factors. Awareness-raising efforts and inter-agency cooperation are expected to improve traffic law enforcement in Jimbaran, Bali.